Differentierad undervisning och integrerade digitala verktyg i förskola och skola: En storskalig studie - Lundqvist, Johanna; Sandström, Margareta; Franzén, Karin; Wetso, Gun-Marie; Larsdotter Bodin, Ulrika; Runström Nilsson, Petra; Munter, Ann-Charlotte (Utbildning & Lärande, 2021)
In Swedish preschool and school classrooms, all children should be offered an education that includes instruction and digital devices. The instruction should be meaningful and interesting for all children, and the digital devices should facilitate teachers’ work and children’s learning. This study concerns differentiated instruction as well as uses and possible benefits gained by digital devices in Swedish preschools and school classrooms. The study is part of a large-scale co-produc-tion project between academy and the surrounding society. Sixty-seven teachers and head-teachers, who value digital devices, participated, and shared their experiences and views on these two matters. A qualitative research approach, including research circles and thematic analyses, was used. The themes prove, for example, the importance of acknowledging children’s interests, joint exploration, provision of parallel support as well as extra challenges, association to children’s previous experi-ences and integration of digital devices of various kind. The result of the study can form a basis for interesting preschool and school discussions. It has relevance for teachers and head-teachers in training, researchers in special education as well as for those who are interested in differentiated instruction and the integration of digital devices.